2002
DOI: 10.1152/ajpregu.00398.2001
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic metabolism in carotid bodies and high-altitude acclimatization in female rats

Abstract: We tested the hypothesis that ovarian steroids stimulate breathing through a dopaminergic mechanism in the carotid bodies. In ovariectomized female rats raised at sea level, domperidone, a peripheral D2-receptor antagonist, increased ventilation in normoxia (minute ventilation = +55%) and acute hypoxia (+32%). This effect disappeared after 10 daily injections of ovarian steroids (progesterone + estradiol). At high altitude (3,600 m, Bolivian Institute for High-Altitude Biology-IBBA, La Paz, Bolivia), neutered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
54
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 29 publications
14
54
2
Order By: Relevance
“…As previously reported by numerous studies (25,26,39,40), females reached higher levels of ventilation and have a lower hematological response than males after chronic exposure to hypoxia. This sex difference is mostly mediated by endogenous ovarian steroids, which act both on the central nervous system (7,8) and on peripheral chemoreceptors to increase ventilatory output (17,23,26,49).…”
Section: Interaction Between Sex and Long-term Consequences Of Neonatsupporting
confidence: 75%
See 2 more Smart Citations
“…As previously reported by numerous studies (25,26,39,40), females reached higher levels of ventilation and have a lower hematological response than males after chronic exposure to hypoxia. This sex difference is mostly mediated by endogenous ovarian steroids, which act both on the central nervous system (7,8) and on peripheral chemoreceptors to increase ventilatory output (17,23,26,49).…”
Section: Interaction Between Sex and Long-term Consequences Of Neonatsupporting
confidence: 75%
“…As discussed above, this could be due to a stronger effect of ventilatory desensitization processes during chronic hypoxia. Experimental studies performed to date are all consistent in showing that reduced minute ventilation in chronic hypoxia is accompanied by an increased Ht, Hb, and/or plasma erythropoietin level (25,26,48), and the negative correlation between minute ventilation and hematological values as show in Fig. 4 is a clear example of this acclimatization balance in rats.…”
Section: Long-term Consequences Of Neonatal Hypoxia In Adultsmentioning
confidence: 56%
See 1 more Smart Citation
“…In rats, females had lower mass-corrected f R than males, but V T and V˙E were similar (either mass-specific or mass-corrected data). Higher values of V˙E and V T in females compared with males likely reflects the respiratory stimulant effect of ovarian steroids (Joseph et al, 2002), and have been reported in our previous studies (Lumbroso et al, 2012). The fact that sex-specific effects were not reported in the present study in rats might be related to the reduced sample size (six males, six females), while we compared 17 males with 16 females in our previous study (Lumbroso et al, 2012).…”
Section: Respiratory and Metabolic Responses To Hypoxia In High Altitmentioning
confidence: 46%
“…Regarding the chemoreflex, data from castrated male cats suggest that testosterone increases the hypoxic and hypercapnic ventilatory responses and augmented carotid body sensitivity to hypoxia (Behan et al, 2003). In adult rats, however, castration had no effect on the ventilatory response measured at the end of hypoxia (Joseph et al, 2002). On the other hand, Bairam et al (2009) demonstrated that gonadectomy increased the acute breathing frequency response to hypoxia in neonatal rats.…”
Section: Testosteronementioning
confidence: 97%